Cine y videojuego Avalon de Mamoru Oshii: Habitar la ficción - Rodríguez Jiménez, Leda (2012)
The article presents an approach to the relationships between cinema and videogames, then focuses on a psychoanalytic reading of the film Avalon by Japanese movies director Mamoru Oshii. Where does the reality end and the game begins? It is the key question which allows us to deploy the hermeneutical discourse towards a reflection on topics as broad and complex as the dialectic between reality and fiction or as specific as anorexia and addiction and their connection with sexuality. To analyse the filmic text from a psychoanalytic perspective, means considering, above all, the problem of desire in the construction of subjectivity. Finally, the textual analysis spreads to one of the most recurring and complex topics of contemporary theory: the aspiration of dispensing of the organic body in an impossible bet or attempt to make a consciousness inhabit the fiction deployed by virtual environments.